Cultural Heritage, Sustainable Tourism and Urban Regeneration : Capturing Lessons and Experience from Japan with a Focus on Kyoto - World Bank Group (World Bank, Washington, DC, 2018)
The World Bank Group (WBG) has long recognized that the restoration and preservationof cultural heritage, urban regeneration, and sustainable tourism can play a vital role in developing countries’ efforts to promote local economic development, accelerate social integration, and alleviate poverty. Against this backdrop, this research report sheds light on lessons learned from the development experience of Kyoto City, the imperial capital of Japan for more than a thousand years and home to 14 well conserved UNESCO World Heritage sites and many historic districts.